2022
DOI: 10.1111/jnc.15588
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2‐G2019S mice display alterations in glutamatergic synaptic transmission in midbrain dopamine neurons

Abstract: The progressive degeneration of dopamine (DA) neurons in the substantia nigra compacta (SNc) leads to the emergence of motor symptoms in patients with Parkinson's disease (PD). To propose neuroprotective therapies able to slow or halt the progression of the disease, it is necessary to identify cellular alterations that occur before DA neurons degenerate and before the onset of the motor symptoms that characterize PD. Using electrophysiological, histochemical, and biochemical approaches, we have examined if glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 59 publications
6
22
1
Order By: Relevance
“…Cells that did not meet these criteria, or that met criteria for DA neurons were not further recorded and were not included in the analyses. The recorded neurons are likely to be GABAergic, and not DA, given that their electrophysiological properties were similar to those described in previous studies [ 6 , 13 , 17 , 18 , 19 , 20 , 21 ], and that the GABAergic nature of recorded neurons in the SNr was confirmed by histochemical and molecular analyzes [ 22 , 23 , 24 ]. For voltage-clamp recordings, patch electrodes (3–5 MΩ) were filled with a solution containing (in mM): 140 CsCl, 2 MgCl 2 , 1 CaCl 2 , 10 HEPES, 10 EGTA, 2 MgATP, 0.3 Na 3 GTP, pH adjusted to 7.3 with CsOH.…”
Section: Methodssupporting
confidence: 81%
See 4 more Smart Citations
“…Cells that did not meet these criteria, or that met criteria for DA neurons were not further recorded and were not included in the analyses. The recorded neurons are likely to be GABAergic, and not DA, given that their electrophysiological properties were similar to those described in previous studies [ 6 , 13 , 17 , 18 , 19 , 20 , 21 ], and that the GABAergic nature of recorded neurons in the SNr was confirmed by histochemical and molecular analyzes [ 22 , 23 , 24 ]. For voltage-clamp recordings, patch electrodes (3–5 MΩ) were filled with a solution containing (in mM): 140 CsCl, 2 MgCl 2 , 1 CaCl 2 , 10 HEPES, 10 EGTA, 2 MgATP, 0.3 Na 3 GTP, pH adjusted to 7.3 with CsOH.…”
Section: Methodssupporting
confidence: 81%
“…Further, in LRRK2-G2019S mice analyzed at postnatal day 21, increased glutamatergic synaptic transmission onto spiny projection neurons was accompanied by hyperexcitability, and these changes were blocked by an LRRK2 kinase inhibitor suggesting their dependency on altered LRRK2 function [ 12 ]. In line with this suggestion, we recently demonstrated that acute treatment with an LRRK2 kinase inhibitor recovered the altered glutamate release on SNc-DA neurons and the increased sEPSC amplitude in DA neurons from the ventral tegmental area to levels similar to those measured in WT mice [ 13 ].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations